Production Performance of Sheep with Pineapple Peel Silage-Based Ration - Mumin, Achmad Raisman Saeful; Riyanti, Lilis; Putra, Kenedy (Jurnal Peternakan, 2025)
TABSTRACT.  The study aimed to analyze the effect of pineapple peel silage in the ration on production performance and to assess the income level of sheep farmers using pineapple peel silage as a based ration. The study was designed in randomized block design with 3 treatments and 3 replications. The treatments consisted of P0 = control diet with 100% field grass, P1 = field grass + pineapple peel silage with 3% of rice bran, and P2 = field grass + pineapple peel silage with 6% rice bran. The diet ratio of grass to pineapple peel silage in the diet was 80:20. Variables measured included dry matter intake, daily weight gain, feed efficiency and Income Over Feed Cost (IOFC). The results showed that the dry matter intake of sheep treated with P1 was significantly higher (P<0.05) than that of P0 and P2. The daily weight gain of sheep treated with P2 was 70.83 g/day, which was not significantly different from P0 and P1 but had a higher numerical value. Feed efficiency and IOFC did not show significant difference (P>0.05). The results of the economic analysis indicated an increase  in farmer income with the use of silage, particularly at P2 with an income of IDR 534,284. In conclusion, the use of pineapple peels silage as ration for sheep increased dry matter intake and had a possitive impact on farmer income.